Efficacy of Pleuran (β-Glucan from Pleurotus ostreatus) in the Management of Herpes Simplex Virus Type 1 Infection. (13th April 2020) - Urbancikova, Ingrid; Hudackova, Dana; Majtan, Juraj; Rennerova, Zuzana; Banovcin, Peter; Jesenak, Milos
Abstract : One of the highly prevalent viral pathogens among children and adults causing infection, clinically presenting as herpes labialis, is herpes simplex virus type 1 (HSV-1). The long-term administration of acyclovir, a standard regimen for therapy against HSV-1 infections, can cause viral resistance against this drug. Therefore, the development of natural drugs with low toxicity that are able to enhance host antiviral defense against HSV infection is needed. β -Glucans represent a type of biologically active molecules possessing antiviral properties. The goal of this study was to investigate the clinical and immunomodulatory effect of β -glucan pleuran (insoluble β -1, 3/1, 6-D-glucan isolated from Pleurotus ostreatus ) based supplements on the duration and intensity of herpes symptoms and on the incidence rate and duration of acute respiratory symptoms and intercurrent diseases in HSV-1 positive patients. Ninety patients were randomised into active and placebo groups. Active treatment with pleuran in systemic application caused a significantly shorter duration of herpes simplex symptoms compared to the placebo group. During the preventive phase (120 days), the duration and severity of respiratory symptoms were lower in the active group compared to the placebo group; however, a significant difference was found only in the case of cough. No significant side effects were observed during both phases of the clinical trial (acute and preventive). Obtained results suggest that the use of pleuran seems to be a promising approach in the treatment of acute HSV-1 with beneficial effect on the respiratory tract symptoms and infections.